Mechanical Effect of Shear Wave Stimulation of Facial Skin - Randrianavony, Koloina; Thieulin, Coralie Privet-; Sigaudo-Roussel, Dominique; Zahouani, Hassan (Archives of Clinical and Biomedical Research, 2026)
Introduction: The Shear Wave Stimulation (SWS) is a novel massage method that permits to stimulate the skin without contact using blasts of air to induce shear and compression waves in the different layers of the skin. This technique uses the principles of mechanotransduction to induce mechanical changes in the skin’s properties, leveraging the cells capacity to transform mechanical stimulus into biochemical reactions. Methodology: This study was conducted on the cheeks of 20 healthy women aged between 20 and 60 years old. To assess the impact of the SWS on the mechanical properties of the skin, the skin’s shear modulus was measured using the UNDERSKIN device. The impact of different stimulation parameters has also been investigated using two opening times of 20ms and 50ms. Results: The measurements revealed that the SWS lead to a significant improvement in the cheek’s skin mechanical properties with an increase in shear modulus of 15% (p=0.010) in the epidermis and a considerable increase of 18% (p<0.0001) in the dermal layer using an opening time of 20ms. Conclusion: The SWS is a non-contact and non-invasive method that can be used to enhance the facial skin mechanical properties. It has also been found that the choice of stimulation parameters plays an important role and should be chosen according to the situation.